2019
DOI: 10.1098/rsfs.2018.0077
|View full text |Cite
|
Sign up to set email alerts
|

Prostate-specific antigen glycoprofiling as diagnostic and prognostic biomarker of prostate cancer

Abstract: The initial part of this review details the controversy behind the use of a serological level of prostate-specific antigen (PSA) for the diagnostics of prostate cancer (PCa). Novel biomarkers are in demand for PCa diagnostics, outperforming traditional PSA tests. The review provides a detailed and comprehensive summary that PSA glycoprofiling can effectively solve this problem, thereby considerably reducing the number of unnecessary biopsies. In addition, PSA glycoprofiling can serve as a prognostic PCa biomar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
60
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(66 citation statements)
references
References 70 publications
0
60
0
Order By: Relevance
“…Thus, from Table 3 and Table 4, it is observed that measurements of the TE concentrations, Zn/TE concentration ratios, and some other TE combinations in EPF could become a powerful diagnostic tool when seeking PCa. To a large extent, continuation of the search for new methods for early diagnosis of PCa was due to experience gained after a critical assessment of the limitations of the current PSA blood serum tests [5]- [11] [41]. In addition to the PSA test and morphological study of needle-biopsy cores of the prostate, the development of highly precise less invasive testing methods will clearly be very useful.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, from Table 3 and Table 4, it is observed that measurements of the TE concentrations, Zn/TE concentration ratios, and some other TE combinations in EPF could become a powerful diagnostic tool when seeking PCa. To a large extent, continuation of the search for new methods for early diagnosis of PCa was due to experience gained after a critical assessment of the limitations of the current PSA blood serum tests [5]- [11] [41]. In addition to the PSA test and morphological study of needle-biopsy cores of the prostate, the development of highly precise less invasive testing methods will clearly be very useful.…”
Section: Discussionmentioning
confidence: 99%
“…The survival rate is proportional to the stage reached at diagnosis; hence early-stage diagnosis using effective diagnostic tools is a key to reducing mortality due to PCa [5]. It is widely acknowledged that screening and early diagnosis of PCa are of vital importance for improving the likelihood of recovery.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Accordingly, it is important to find biomarkers that meet the following criteria: (1) adequate half-life with stability within the bloodstream; (2) the presence in blood/urine in sufficient concentration; and (3) the presence in all TC types, irrespective of age, the localisation and histological profile [32]. A full list of what is required for the biomolecules to become a biomarker can be found elsewhere [33].…”
Section: Tc Biomarkers and Their Limitationsmentioning
confidence: 99%
“…The comprehensive review by Tkac et al provides important information that prostate-specific antigen (PSA) glycoprofiling can also be implemented as a diagnostic prostate cancer biomarker in serum [11]. Specific glycoforms can be detected with already validated commercial lectins and provides significant advantage over PSA currently used in clinics.…”
mentioning
confidence: 99%